Assessment of body mass reduction in patients qualified for elective cardiac operations in Cardiac Surgery Department, Pomeranian Medical University, Szczecin, Poland – preliminary report - Zamojska, Ewa; Majewski, Włodzimierz (Pielęgniarstwo Chirurgiczne i Angiologiczne/Surgical and Vascular Nursing, 2008)
Background: An extensive health prevention programme is being conducted in the Cardiac Surgery Department. A current decision about operation is undertaken after estimation of operative risk and body mass index (BMI in kg/m 2 ) value. According to BMI reduction of body mass to the correct value was recommended to the patients. Aim of the study: Assessment of reduction of BMI in patients qualified for elective cardiac operations in the Cardiac Surgery Department in Szczecin. Material and methods: A prospective study comprised 200 patients (141 males and 59 females) qualified for cardiac surgery from February to May 2008. All patients had a physical examination with BMI count in the outpatient clinic and another time BMI assessment at admission to the department. Time from qualification visit to admission for cardiosurgery was 4 to 6 weeks. Results: BMI on first visit was from 19.59 to 44.19 mean 28.8 in males, and from 19.71 to 38.41 mean 27.78 in females. Altogether 80 males and 29 females reduced their weight according to the doctor’s recommendations. Mean degree of BMI changes dropped in males by 0.65 kg/m 2 and increased in female patients by 0.12 kg/m 2 . Conclusions: More than half (109) of patients reduced their body weight in compliance with medical personnel, but in 91 there was no compliance. The goal of prophylaxis was achieved in 58.8% of men and in 45.3% of women, generally in 54.5% of patients.